Penerapan Pendekatan Deep Learning Berbasis Smart TV dalam Meningkatkan Student Engagement pada Pembelajaran Matematika di SMP 4 Rejang Lebong - Siti Nabilah; Akbar Effendi; Syaripah (JUMAT: Jurnal Matematika, 2026)
Conventional methods that remain dominant in mathematics instruction tend to render students passive, prone to boredom, and challenged by abstract concepts. This study aims to describe the implementation of a Smart TV-based "Deep Learning Approach" to enhance student engagement in mathematics lessons. In this context, the term "deep learning" refers to a pedagogical approach rather than the field of Artificial Intelligence. The study employed a qualitative, descriptive design and was conducted at SMP Negeri 4 Rejang Lebong between May and June 2026. The participants included one mathematics teacher and 26 students from class VIII B. Data were collected through observation, interviews, and documentation, and subsequently analyzed using data reduction, data presentation, and conclusion-drawing techniques. The findings indicate that the implementation of the Smart TV-based Deep Learning Approach successfully enhanced student engagement across behavioral, emotional, and cognitive dimensions. Students demonstrated active participation by asking questions, engaging in discussions, and grasping mathematical concepts; they were also able to relate lesson material to real-life situations through the use of visual media, videos, animations, and contextual learning activities. Thus, the Smart TV-based Deep Learning Approach serves as an effective instructional alternative for boosting student engagement and fostering a more meaningful mathematics learning experience.